Assistance for Waste Management Cadres at the As Salafiyah Al Fitrah Islamic Boarding School Surabaya - Rusdi, Warda Elmaida; Masithah, Dewi; Anggarsari, Yasi; Rhomadhoni, Muslikhah Nourma; Farakhin, Noer (Community Development Journal, 2022)
Background: Waste is a form of a productderived from human activity or activity in liquid, solid, or gaseous form. Currently, solid waste is a serious problem for people, especially in urban communities because the amount continues to increase every year. Some of the impacts, such as environmental pollution, both soil, water and air pollution, sources of disease spread, as well as their impact on global warming and climate change in the world. The initialsurvey conducted found thatmost of thestudents ofPondok Pesantren As Salafiyah Al Fitrah Surabaya had scattered and poorly managedwaste. This condition is caused by the lackofknowledge and overall awarenessofstudents aboutwastemanagement.This activity aims to increasestudent’sawareness and knowledgeaboutwaste management. The implementation of this community service usestheapproach methodofempowering studentcadrestotalling21 studentsthroughassistance related towastemanagementat the As Salafiyah Al Fitrah Islamic Boarding School Surabayathrougheducational activities,training, mentoringand providinginformation mediaforwaste managementwith a 3 R model (Reduce, Reuse, Recycle) in the form of modules and postersEvaluation instrumentsuse pre questionnaires and test posts while forseeingthedifference in activityindicatorswhile the effectivenessofthe overall implementation of activitieswas tested with statistics usingthe Wilcoxon Test with a p-value of 0.021 < 0.05. Meanwhile, differences inchanges in knowledge, attitudes and behaviourofstudentswere assessed with the results of differences in averagescoresfrom 56 to 75. Conclusion: there was a change in knowledge after community service was carried out in the form of cadre assistance related to waste management in the As Salafiyah Al Fitrah Islamic Boarding School Surabaya environment.